Pengukuran dan Evaluasi Kualitas Layanan Perguruan Tinggi Menggunakan Metode Fuzzy Delphi, Fuzzy Service Quality, dan Fuzzy AHP - Saputra, Saputra; Indrapriyatna, Ahmad Syafruddin; Jonrinaldi, Jonrinaldi (Fakultas Teknik Universitas Tulang Bawang, 2026)
The quality of higher education services is a key factor in enhancing student satisfaction and loyalty amid intense competition, especially in private universities. A systematic evaluation of academic services is essential for improving educational quality. This study measures and evaluates the quality of services at a private university in Riau using an integrated model of Fuzzy Delphi, Fuzzy Service Quality, and Fuzzy Analytic Hierarchy Process (FAHP). A total of 47 service quality indicators from the dimensions of Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy have been agreed upon by experts. Indicator A1 (completeness of facilities) has a weight of 0.0837 and a positive gap of 0.0508, while A5 (parking arrangement) has a negative gap of -0.1745. The Reliability dimension shows dissatisfaction with B1 (staff services) with a weight of 0.0545 and a gap of -0.2180. In Responsiveness, C1 (consultation time) has a gap of -0.1784, and C2 (friendliness) has a positive gap of 0.0441 with a weight of 0.2452. In Assurance, D1 (clarity of material delivery) has a weight of 0.2413 and a gap of 0.0502; D4 (accommodation of basic needs) has a gap of -0.1539. In Empathy, E1 (staff attention) has a weight of 0.2741 and a gap of 0.0462; E2 (management involvement) has a gap of -0.1715. These results identify critical areas and aspects that need to be maintained, serving as a basis for strategic decision-making to improve the quality of higher education services. Keywords: Fuzzy AHP, Fuzzy Delphi, Fuzzy Service Quality, Higher Education, Service Quality